18 UMPSA volunteers join Kashmir Humanitarian Mission to repair bridges and improve access for residents - Nur Husna, Azlan (UMPSA, 2024)
KASHMIR, INDIA, 7 October 2024 – In a heartfelt effort to make a meaningful impact, 18 volunteers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), including staff and students, embarked on a humanitarian mission to Kashmir, India, under the International Mobility Travel Programme.